“It is necessary to act with extreme caution in order to protect the soviet authorities from any accusations of interference in religious affairs”. An unknown document of the State Political Directorate on instigating the split in the Russian Orthodox Church - Savin Andrey (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article introduces a new document of the GPU Secret Department on the instigating the Renovationist split in the Russian Orthodox Church. This is the postal telegram No. 24968s of May 29, 1922, signed by the Head of the Secret Operative Directorate of the GPU V. R. Menzhinsky, and by the Head of the Secret Department of the GPU T. P. Samsonov. This telegram is part of a set of directives issued by the GPU, which initiated and regulated the church schism in 1922. Earlier, the researchers at Orthodox Svyato-Tikhonovsky University of Humanities published two directives of the GPU Secret Department, sent out from Moscow in the summer and fall of 1922. The documents describes the specific role that the GPU played in the beginning of the campaign to instigate split in spring-summer of 1922. In particular, the telegram deals with the actions of the GPU at the very beginning of the campaign. The document shows that by this time, the leadership of the GPU had already developed two main strategies, which they then adhered to steadily during the campaign: complete secrecy and strict control over the actions of the renewed clergy. The publication also describes specific measures taken by the GPU in Siberia immediately after receiving the Circular of May 29, 1922: the establishment of the renovationist Siberian church department ("Sibtserkov’") and the trials of the Tomsk Vicar and Barnaul Archbishop Victor (Bogoyavlensky) and the Irkutsk and Verkholensk Archbishop Anatoly (Kamensky).